Diversity and phylogenetic analyses of bacteria from a shallow-water hydrothermal vent in Milos island (Greece) - Giovannelli, Donato; d'Errico, Giuseppe; Manini, Elena; Yakimov, Michail; Vetriani, Costantino (Frontiers in Microbiology, 2013)
Studies of shallow-water hydrothermal vents have been lagging behind their deep-sea counterparts. Hence, the importance of these systems and their contribution to the local and regional diversity and biogeochemistry is unclear. This study analyzes the bacterial community along a transect at the shallow-water hydrothermal vent system of Milos island, Greece. The abundance and biomass of the prokaryotic community is comparable to areas not affected by hydrothermal activity and was, on average, 1.34 × 108 cells g−1. The abundance, biomass and diversity of the prokaryotic community increased with the distance from the center of the vent and appeared to be controlled by the temperature gradient rather than the trophic conditions. The retrieved 16S rRNA gene fragments matched sequences from a variety of geothermal environments, although the average similarity was low (94%), revealing previously undiscovered taxa. Epsilonproteobacteria constituted the majority of the population along the transect, with an average contribution to the total diversity of 60%. The larger cluster of 16S rRNA gene sequences was related to chemolithoautotrophic Sulfurovum spp., an Epsilonproteobacterium so far detected only at deep-sea hydrothermal vents. The presence of previously unknown lineages of Epsilonproteobacteria could be related to the abundance of organic matter in these systems, which may support alternative metabolic strategies to chemolithoautotrophy. The relative contribution of Gammaproteobacteria to the Milos microbial community increased along the transect as the distance from the center of the vent increased. Further attempts to isolate key species from these ecosystems will be critical to shed light on their evolution and ecology.